A review on the current research and application of wastewater source heat pumps in China. (June 2018) - Shen, Chao; Lei, Zhuoyu; Wang, Yuan; Zhang, Chenghu; Yao, Yang
Highlights: Research and application of WWSHPs in China are reviewed and analyzed. Challenges in the applications of WWSHPs and related studies are summarized. The opportunity of WWSHPs is discussed through reviewing related studies. Abstract: Wastewater source heat pumps (WWSHPs) have become increasingly popular in many countries due to their advantages of relatively higher energy utilization efficiency and environmental protection. As concluded in literature (Hepbasli et al., 2014) that "the location where the majority of the studies are conducted is China", but many research results were published in Chinese only. Therefore, the current research and application of WWSHP systems in China or published in Chinese are reviewed in this paper in terms of current projects, challenges, and opportunities of WWSHPs to the best of our knowledge. The WWSHP projects are reviewed first. Next, challenges in the applications of WWSHPs and related studies are presented, including foulant contained in wastewater, fouling deposited on the heat transfer surface, flow and heat transfer characteristics of wastewater, and its temperature and amount. Afterward, the opportunity of WWSHPs is discussed through reviewing the development of special devices and heat exchangers of WWSHPs and the economic benefits. Finally, some concluding remarks are drawn from the review. It is expected that the study in this paper will supplement the knowledge of WWSHPs and provide reference data to the WWSHP researchers all over the world.